Wearable Hybrid Device Capable of Interactive Perception with Pressure Sensing and Visualization. (7th August 2022) - Guo, Yunjian; Li, Hao; Li, Yang; Wei, Xiao; Gao, Song; Yue, Wenjing; Zhang, Chunwei; Yin, Feifei; Zhao, Songfang; Kim, Nam‐Young; Shen, Guozhen
Abstract: A wearable interactive device that can synchronously detect and visualize pressure, stimuli will supplement easily identifiable in situ signals with conventional sensing that outputs only electronic signals. Currently, most interactive devices are composed of physically connected separate pressure sensors and display elements, which do not conform to the development of miniaturization and high integration. The realization of combining these two functions in one device with a simplified configuration is still only beginning to be explored. Inspired by the two‐in‐one response of the octopus, which can both sense and visualize stimuli, an integrated hybrid device based on ionic sensing and electrochromic display is proposed for interactive pressure perception. By efficiently reusing the electrodes and ionic gel, the device enables quantitative sensing and direct color changing in response to pressure. Benefiting from its excellent comprehensive performance, the applications are explored and verified, including the interactive perception of pressure information, hiding and display of visual information under pressure regulation, and repeated writing and erasing on flexible boards. Notably, multiple customized systems with improved design flexibility are implemented to provide remote monitoring and visual warning of behavioral states and physiological parameters. This study diversifies solutions to realize a direct link between pressure detection and visualization. Abstract : Inspired by the two‐in‐one response of the octopus, which can both sense and visualize stimuli, an integrated hybrid device based on ionic sensing and electrochromic display is proposed for interactive pressure perception. By efficiently reusing the electrodes and ionic gel, the device enables quantitative sensing and direct color‐changing in response to pressure. Multiple customized systems with improved design flexibility are implemented to provide remote monitoring and visual warning of behavioral states and physiological parameters.